What Does the Yield Curve Tell Us about Exchange Rate Predictability? - Chen, Yu-chin; Tsang*, Kwok Ping (The Review of Economics and Statistics, 2013)
Since the term structure of interest rates embodies information about future economic activity, we extract relative Nelson-Siegel (1987) factors from cross-country yield curve differences to proxy expected movements in future exchange rate fundamentals. Using monthly data for the United Kingdom, Canada, Japan, and the United States, we show that the yield curve factors predict exchange rate movements and explain excess currency returns one month to two years ahead. Our results provide support for the asset pricing formulation of exchange rate determination and offer an intuitive explanation to the uncovered interest parity puzzle by relating currency risk premiums to inflation and business cycle risks.